Ecologia de girinos de Corythomantis greeningi (Anura: Hylidae) e microalgas em fitotelmos de troncos de árvores - Leal, Cledinaldo Borges (2019)
Fitotelmata are temporary lentic aquatic environments formed by the accumulation of rain in structures of terrestrial plants, constituting peculiar microcosms. Such as all aquatic environments, its trophic base is usually microalgae (phytoplankton and periphyton), controlled by bottom-up factors, especially light and nutrients, and top-down, predators such as zooplankton, fish and amphibian larvae. In the National Forest (NF) of Palmares (Altos, Piauí, Brazil), such environments are the only available water source, crucial for the reproduction of the amphibian Corythomantis greeningi (Anura: Hylidae). The objective of this study was to understand the ecological structuring factors of phytotelmata in tree trunks, as well as the regulating factors of the microalgae and tadpoles of this amphibian, listing possible determinant factors in the choice of phytohelma for spawning and to verify possible relationships between nutrient concentrations and phytotelma species and its phylogenetic classification. Thus, we made eight collections in ten phytotelmata, in two subsequent years (March to April / 2016 and March to April / 2017), with measurement of climatological and hydrological variables, phytoplankton and periphytic biomass and biovolume of tadpoles. The results showed that the main environmental factor for phytotelmata is rainfall, and there is also influence of the plant species, and that turbidity is the factor that most explains the size variations of tadpoles, as well as the choice of spawning locations. The largest amount of phytoplankton occurred in the Dictyoloma vandellianum (pau-de-urubu) phytotelma and the periphyton in the Lecythis pisonis (sapucaia) phytotelma. Bottom-up factors, especially those related to light, contributed 31% to phytoplankton biomass variation, but no evident influence of top-down factors. The periphyton biomass showed no contribution of either bottom-up nor top-down factors. In terms of nutrients, the sapucaia differed from the other species and the jacaranda (Machaerium villosum) was different from the angico branco (Anadenanthera colubrina), a consistent result with the phylogenetic classification of such plants. We conclude that, although phytotelmata are unpredictable environments due to the lack of stability, it is possible to make ecological inferences about the processes which occur in them.